THE EFFECT OF SHORT-SESSION NEUROFEEDBACK THERAPY ON BRAIN WAVE ACTIVITY IN CHILDREN WITH ADHD - Grozny Guevara; Suzy Yusna Dewi; Nunuk Nugrohowati; Nugrahayu Widyawardani; Yasmin Azizah Idhsa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by symptoms of inattention, and distractibility, with or without hyperactivity. According to the CDC, it was the most common mental health disorder among children aged 3-17 years, with a prevalence of 9.8% from 2016 to 2019. Over time, various therapeutic methods have been developed to treat ADHD patients, one of which is neurofeedback therapy. Neurofeedback (NFB) therapy, also known as Neurotherapy, is a type of biofeedback therapy that utilizes feedback from brain activity to optimize brain function in children with ADHD potentially. This study aims to determine the effects of short-session neurofeedback therapy on brainwaves in children with ADHD using the quasi-experimental method. Samples were obtained from medical records of SMR and Theta brainwave activity from the first and fifth sessions of neurofeedback therapy through simple random sampling. A sample size of 30 was calculated and analyzed using a paired sample T-test. The researcher decided to measure changes after 5 sessions because childhood is a very active period, and children have numerous activities, limiting their availability for therapy. It was found that after undergoing neurofeedback therapy for 5 sessions, there was a significant improvement in the patient's SMR wave activity compared to before therapy (p=0.004). However, there was no substantial change in the patient's Theta wave activity before and after the 5 neurofeedback therapy sessions (p = 0.178). The considerable increase in SMR waves indicates an improvement in the patient's ability to concentrate on specific tasks without being easily distracted.